IMPLEMENTASI JARINGAN DENGAN LOAD BALANCING DAN RECURSIVE ROUTE FAILOVER MIKROTIK PADA PT.PELAYARAN NASIONAL INDONESIA - Kristanto, Lian; Raharjo, Mugi (Teknik Informatika Universitas Suryakancana Cianjur, 2024)
Along with the advancement of technology in the field of telecommunications, services to the community have also been based online, as is the case at the PT. Pelni branch office. However, sometimes services are hampered due to sudden internet connection interruptions, so using a failover system assisted by a modem that functions as ISP 2 which is a solution in backing up the internet connection from ISP 1 if it goes offline suddenly. In this study, all clients and users connected to ISP 1 will be directed to ISP 2 using a failover system and the results of all clients or users can be backed up properly and we also do load balancing used to distribute network traffic loads evenly on two connection lines, so that internet performance becomes more balanced and stable. MikroTik plays a role in marking data packets that access the internet and determining the ISP line to be used, as well as distributing the load on both ISPs.